Ceria Nanoenzyme‐Based Hydrogel with Antiglycative and Antioxidative Performance for Infected Diabetic Wound Healing. Issue 11 (6th October 2022) - Cheng, Fang; Wang, Shenqiang; Zheng, Hua; Shen, Haidong; Zhou, Li; Yang, Zuoting; Li, Qiyan; Zhang, Qiuyu; Zhang, Hepeng
Abstract: Diabetic wound healing still faces a dilemma because of the hostile hyperglycemic, oxidative, and easily‐infected wound microenvironment. In addition, advanced glycation end products (AGEs) further impede wound repair by altering the immunological balance. Herein, ceria nanorods with distinctive antiglycative and excellent antioxidative capacities are innovatively introduced into a self‐healing and erasable hydrogel, which could reshape the wound microenvironment by expediting hemostasis, inhibiting infection, reducing AGEs, and continuously depleting reactive oxygen species. The remitted oxidative stress and glycosylation synergistically regulate inflammatory responses, and promote revascularization and extracellular matrix deposition, resulting in accelerated diabetic wound repair. This study provides a highly efficient strategy for constructing nanoenzyme‐reinforced antiglycative hydrogel that regulates every wound healing stage for diabetic wound management. Abstract : Easy infection and severe inflammation make diabetic wounds difficult to heal. A nanoenzyme‐reinforced hydrogel is fabricated for facilitating infected diabetic wound repair. The hydrogel with antiglycative, antioxidative, and antibacterial activities comprehensively modulates the hostile wound microenvironment. In vivo studies verify that the prepared hydrogel promotes multiple stages, including hemostatics, inflammation, proliferation, and tissue remodeling, thereby accelerating diabetic wound healing.